A physical explanation for the magnetic decrease ahead of dipolarization fronts - Z. H. Yao; J. Liu; C. J. Owen; C. Forsyth; I. J. Rae; Z. Y. Pu; H. S. Fu; X.-Z. Zhou; Q. Q. Shi; A. M. Du; R. L. Guo; X. N. Chu (Annales Geophysicae, 2015)
Recent studies have shown that the ambient plasma in the near-Earth magnetotail can be compressed by the arrival of a dipolarization front (DF). In this paper we study the variations in the characteristics of currents flowing in this compressed region ahead of the DF, particularly the changes in the cross-tail current, using observations from the THEMIS satellites. Since we do not know whether the changes in the cross-tail current lead to a field-aligned current formation or just form a current loop in the magnetosphere, we thus use redistribution to represent these changes of local current density. We found that (1) the redistribution of the cross-tail current is a common feature preceding DFs; (2) the redistribution of cross-tail current is caused by plasma pressure gradient ahead of the DF and (3) the resultant net current redistributed by a DF is an order of magnitude smaller than the typical total current associated with a moderate substorm current wedge (SCW). Moreover, our results also suggest that the redistributed current ahead of the DF is closed by currents on the DF itself, forming a closed current loop around peaks in plasma pressure, what is traditionally referred to as a banana current.